2022
DOI: 10.1108/ijchm-10-2021-1273
|View full text |Cite
|
Sign up to set email alerts
|

Online food delivery research: a systematic literature review

Abstract: Purpose Online food delivery (OFD) has witnessed momentous consumer adoption in the past few years, and COVID-19, if anything, is only accelerating its growth. This paper captures numerous intricate issues arising from the complex relationship among the stakeholders because of the enhanced scale of the OFD business. The purpose of this paper is to highlight publication trends in OFD and identify potential future research themes. Design/methodology/approach The authors conducted a tri-method study – systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…However, this research only considered intentions related to the general usage of OFDS and did not focus on any digital platform and/or brand (Gunden et al , 2020). A systematic literature review of OFDS indicated cloud kitchens as a revenue stream for restaurant operators (Shroff et al , 2022). However, none of these studies have specifically examined the use of OFDS in the context of cloud kitchens, so the current study plans to address this gap in the literature.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…However, this research only considered intentions related to the general usage of OFDS and did not focus on any digital platform and/or brand (Gunden et al , 2020). A systematic literature review of OFDS indicated cloud kitchens as a revenue stream for restaurant operators (Shroff et al , 2022). However, none of these studies have specifically examined the use of OFDS in the context of cloud kitchens, so the current study plans to address this gap in the literature.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…In the next paper titled "Online food delivery research: A systematic literature review," Shroff et al (2022) conducted a tri-method study using systematic literature review, bibliometric and thematic content analysis of 43 articles on online food delivery (OFD) published in 24 journals from 2015 to 2021. Six potential research themes were identified.…”
Section: Purposementioning
confidence: 99%
“…For restaurant owners and managers to increase sales and boost customer happiness, it is imperative that they comprehend the impact of customer evaluations on purchasing choices. Understanding the elements that influence restaurant popularity and customer reviews on the site can also enable Zomato to better serve its users and partners.The online food delivery industry is rapidly growing across the world, and India is no exception [10][11]. With the emergence of various online food delivery platforms like Zomato, Swiggy, Foodpanda, and others, people can easily order food online and get it delivered to their doorstep.…”
Section: Introductionmentioning
confidence: 99%